Finite-time control design for a quadrotor transporting a slung load. (May 2022) - Lv, Zongyang; Zhao, Qing; Li, Shengming; Wu, Yuhu
Abstract: In this paper, we propose a nonlinear finite-time control strategy to solve the motion control problem for a quadrotor with a slung load (QSL). This work aims to realize high-performance motion control for the QSL, even in perturbations. To improve the dynamic performance and the robustness of the QSL system, a novel nonlinear controller is designed with cascade structure. The finite-time stability of the resulting closed-loop system is theoretically analyzed in this work. Furthermore, the advantages of the proposed control strategy are demonstrated by comparison results with different strategies through simulations in MATLAB/SimMechanics. Finally, the effectiveness of the proposed controller is verified in actual experiments on a specially designed experimental QSL.